Study of torque matching of revolving vane compressor and expander - Subiantoro, A (2016)
An investigation was carried out to find the most optimum configuration, particularly the torque matching characteristics, of an integrated Revolving Vane compressor- expander. To carry out the study, a mathematical model of the integrated compressor-expander was developed. An open cycle air refrigeration system was adopted. The controlled parameter was the angle shift between the compressor and the expander. The observed parameters were the peak torque requirement and the bearing load. The results show that when properly matched, the peak torque can be reduced by more than 65% while the bearing loads can be reduced by up to 25%, depending on operating conditions. Unfortunately, the optimum angle shifts for peak torque do not always coincide with those for bearing load. When the pressure and inertial components of the torques are comparable or when the inertial component is dominant, the optimum angle shifts for peak torque and bearing load are around 180° and 330°, respectively. When the pressure component is dominant, the optimum angle shift for peak torque is equal to the angle difference between the pressure peak torques of the compressor and the expander while for bearing load is around 150°.